The Changing Logic of Political Citizenship: Cross-National Acquisition of Women's Suffrage Rights, 1890 to 1990 - Ramirez, Francisco O.; Soysal, Yasemin; Shanahan, Suzanne (American Sociological Review, 1997)
Francisco O. Ramirez, Yasemin Soysal, Suzanne Shanahan, The Changing Logic of Political Citizenship: Cross-National Acquisition of Women's Suffrage Rights, 1890 to 1990, American Sociological Review, Vol. 62, No. 5 (Oct., 1997), pp. 735-745